Representations of Māori in colonial health policy in Aotearoa from 2006-2016: a barrier to the pursuit of health equity. Issue 3 (27th May 2021) - Came, H. A.; Herbert, S.; McCreanor, T.
ABSTRACT: An integral part of colonisation is the suppression and marginalisation of indigenous knowledges. The indigenous health system within Aotearoa (New Zealand) was supplanted with a colonial infrastructure and praxis which has proven ineffective in addressing systemic health inequities created by the processes of colonisation. This novel study interrogates discursive representations of Māori (Indigenous peoples of Aotearoa) within colonial public health policy between 2006 and 2016. Colonial policy refers to generic or mainstream policy that are designed for 'all' New Zealanders. We utilised thematic analysis to examine 106 policies and, after excluding 13 ethnic specific policies, identified 68 policies containing no mention of Māori. The analysis highlights five themes relating to discursive representations of Māori. These were: i) silence about Māori health; ii) Māori as especially at risk; iii) Crown (lack of) responsiveness to te Tiriti o Waitangi obligations; iv) recognition of Māori philosophical approaches to service provision; and v) utilising mātauranga Māori (Māori knowledge). These findings suggest colonial policy presents a barrier to the pursuit of health equity and is poorly aligned to global Indigenous human rights declarations. Within the context of Aotearoa it echoes the sentiments of the key Waitangi Tribunal [WAI 2575] finding that health policy is contributing to health inequities and failing Māori. Health policy must be decolonised to better engage with human rights declarations and te Tiriti o Waitangi obligations in order to achieve health equity.